Pengaruh likuiditas pendanaan terhadap pengambilan risiko pada Bank Perkreditan Rakyat syariah di Indonesia - Maizul Rahmizal; Irdha Yusra; Laynita Sari (Jurnal Kajian Manajemen Bisnis, 2022)
Islamic bank is one of the financial institutions that is managed with the basics of sharia in the form of values and concepts. Every financial institution is inseparable from risk. This study investigates the connection between bank risk-taking and funding liquidity. Quantitative data from the Financial Services Authority (OJK) in the form of BPR Syariah financial statements for the years 2016 to 2020 were used in this study. We will estimate the panel data model to examine the relationship between the independent variable, namely funding liquidity to bank risk at Islamic rural banks in Indonesia. The study's findings indicate that funding liquidity affects bank risk taking in three different ways: negatively and significantly through risk weighted assets, positively and significantly through loan loss provisions, and positively and insignificantly through Z-Score. The increase in risk can be prevented by increasing bank capital and carrying out more measurable credit expansion.